Microstructure, electrical properties, bioactivity, biocompatibility and osteogenic differentiation ability of bio-piezocomposite fabricated by hydroxyapatite and (Ba,Ca)(Ti,Sn)O3-based ceramics - Geng Tang; Hong Yang; Bingqing Zhao; Dunying Wang; Fangfang Zeng; Qibin Liu (Journal of Materials Research and Technology)
The rapid repair of bone defects remains a challenging clinical goal, with bio-piezoelectric composites emerging as promising materials due to their ability to replicate bone's natural composition and electrical functionality. This study developed hydroxyapatite (HA)-based composites incorporating (Ba,Ca)(Ti,Sn)O3-based piezoceramics, achieving piezoelectric coefficients of 28.7 ± 2.48 pC/N, 11.1 ± 0.57 pC/N, and 5.7 ± 0.98 pC/N at HA mass fractions of 10%, 20%, and 30%, respectively, with a porosity around 20%. The composites were synthesized with a solid-state sintering method. The phase structure, surface morphology, and ferroelectric domain configuration of the composites were characterized. Electrical properties, compressive strengthen, hydrophilicity, in vitro bioactivity, biocompatibility and osteogenic ability were assessed. X-ray diffraction (XRD) analysis confirmed that all composites consisted of perovskite structure and HA phases. Microscopic observations revealed the (Ba,Ca)(Ti,Sn)O3-based piezoceramics particles embedded within the HA matrix. Evenly dispersed, irregular pores were formed, and pore size decreased as the HA content increased. The composite with 20 wt% HA exhibited dense, small wedge-shaped domains and ferroelectric orthogonal (O) phase. Importantly, these composites demonstrated favorable compressive strength, surface wettability and biocompatibility, along with enhanced bioactivity and osteogenic differentiation ability in vitro, underscoring their potential in bone tissue engineering applications.